Development of 3-dimentional micropatterned scaffolds for osteogenesis and chondrogenesis of mesenchymal stem cells - Liaw, Yin Siang (2014)
For years, the concept of harvesting autologous Mesenchymal Stem Cells (MSCs) and applying them for regenerative medicine has been extensively studied. Numerous researchers have conducted investigations on the use of topography to stimulate in-vitro MSCs differentiation into different types of cells. However, the main limitation of previous studies on topographical factors is that the investigations has been done on typical monolayer culture system and is only limited to 1-2 layer of cells sheet formation. This poses challenges on feasibility of translation into clinical application like implantation into 3D defect site and integration to existing tissue. The objective of this project is to develop 3-Dimensional micro-patterned structures to study the effect of topographies cues to osteo- and chondrogenesis of MSCs. The scaffold was created by incorporating the topographies on the side of the wall instead of the bottom of scaffolds. Cell morphological analysis by actin cytoskeleton and nuclei counterstaining revealed that cell nuclei are flatter in scaffold without topography and more rounded in scaffold with topography. Besides that, F-actin cytoskeleton is less aligned in topographical scaffold while showing higher degree of alignment with the smoother wall. It can be deduced that MSCs exhibit higher degree of cell-cell interaction when topography is present.